(untitled) (Fiep Bulletin - online, 2013)
The objective of this study is to recognize the ritual aspects and the show on the speech of the dancers´ actors at Deborah Colker Company. It is a descriptive and explorative study, with qualified identification. Four interviews were performed, making usage of association of ideas to inductive words: dance, show, illusion, body, training, risk, Route, speed, stage and public. This projective technique tries to catch what symbolical the individual has. The qualified exam of similarity, the difference and the continuity among ideas, permitted the punctuation of relations among elements which brought out the senses of these dancers. The representations of Deborah Colker contemporary dancer´s company are considered completed. For this “completion” we mean according to Almeida (2008), the series of typical manifestations of the contemporary world which tries to involve elements from the show (static), ritual (synestatic) and contemplation. Actors and spectators. Both involved in the action of the show, in such a way, interact in a typical ritual element. That one, has a essential focus the practitioner that, in his/her activity, may develop different levels of synestactic intensions, which is not totally accessible for those who contemplate because that mobilizes the subjectivity of the actor. Although the performance has not been totally made to be ritualized, that may happen. The show art, like dancing, is made to be seen, it is expressive and has the aim to touch the spectator and as a language, to communicate a message. Ritual and show, known by the perspective of development and as generating events of complex sensorial processes imply the idea of sensorial glass (ALMEIDA, 2008). The common association were: energy, tough way, essential, art, ideal physics, imagination, pleasure, concentration and show. The stage, at the dancing show, represents a secrete place. The ritual is lived by those dancers who feel their energies flow until get the spectator that gets involves in a dancer/spectator communion.